Type VI B choledochal cyst: a rare entity - Joshi, Sampada V.; Bakhshi, Girish D.; Sable, Chandrakant; Dutt, Aishwarya S.; Baligar, Sushrut S.; Jha, Madhu Kumari (International Surgery Journal, 2022)
Choledochal cysts (CDC) are congenital dilatations of extra hepatic biliary system with or without involving intrahepatic bile ducts. Traditionally classified into five types with emerging type VI, involving dilatation of cystic duct, which is the rarest. It is seen in middle-aged females. Most are symptomatic with common symptom being abdominal pain. Magnetic resonance cholangiopancreatography (MRCP) is diagnostic. Surgical treatments range from cholecystectomy to Roux en Y hepaticojejunostomy. They are at a risk of malignant transformation. Hence should be looked for when encountered with congenital biliary system anomalies. We presented a case of a young male with type VI B CDC and its management. A brief case report with review of literature is presented.